Cash, food, or vouchers? Evidence from a randomized experiment in northern Ecuador - Hidrobo, Melissa; Hoddinott, John F.; Peterman, Amber; Margolies, Amy; Moreira, Vanessa (International Food Policy Research Institute, 2012)
The debate over whether to provide food assistance and the form that this assistance should take has a long history in economics. Despite the ongoing debate, little rigorous evidence exists that compares food assistance in the form of cash versus in-kind. This paper uses a randomized evaluation to assess the impacts and cost-effectiveness of cash, food vouchers, and food transfers. We find that all three modalities significantly improve the quantity and quality of food consumed. However, differences emerge in the types of food consumed, with food transfers leading to significantly larger increases in calories consumed, and vouchers leading to significantly larger increases in dietary diversity.